2023
DOI: 10.1186/s12931-023-02593-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of SARS-CoV-2 infection in patients with cystic fibrosis undergoing CFTR channel modulators treatment: a literature review

Antonio Vitiello,
Michela Sabbatucci,
Andrea Silenzi
et al.

Abstract: Several risk factors for Coronavirus-2019 (COVID-19) disease have been highlighted in clinical evidence. Among the various risk factors are advanced age, metabolic illness such as diabetes, heart disease, and diseases of the respiratory system. Cystic Fibrosis (CF) is a rare disease with autosomal recessive transmission, characterised by a lack of synthesis of the CFTR channel protein, and multi-organ clinical symptoms mainly affecting the respiratory tract with recurrent pulmonary exacerbations. In view of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…There was also increased concern for patients with CF, an inherited, autosomal recessive disorder caused by mutations in the gene encoding the anion channel Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) that can lead to chronic pulmonary infections and respiratory failure. However, COVID-19 incidence estimates in CF were reported to be lower than in the general population with often less severe outcomes than originally anticipated 36,155,156 . In our experimental mouse model, we demonstrate that recent pulmonary infection with S. aureus resulted in significantly enhanced innate control of SCV2 replication.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…There was also increased concern for patients with CF, an inherited, autosomal recessive disorder caused by mutations in the gene encoding the anion channel Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) that can lead to chronic pulmonary infections and respiratory failure. However, COVID-19 incidence estimates in CF were reported to be lower than in the general population with often less severe outcomes than originally anticipated 36,155,156 . In our experimental mouse model, we demonstrate that recent pulmonary infection with S. aureus resulted in significantly enhanced innate control of SCV2 replication.…”
Section: Discussionmentioning
confidence: 91%
“…While certain chronic lung diseases, including tuberculosis (TB) 28,29 and chronic obstructive pulmonary disease (COPD) [30][31][32][33] have been associated with increased severity of COVID-19 in most studies, other chronic pulmonary conditions, such as asthma [32][33][34][35] and cystic fibrosis (CF) [36][37][38] did not consistently correlate with worsened COVID-19 presentation and have even been associated with improved disease outcomes. The immunological factors in the lung that determine such variability in early viral control, and thus the likelihood of developing severe disease, are incompletely understood, and challenging to examine in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…As previously described, CFTR impairment leads to a dysfunction of the environment of the respiratory tract. In recent years, new drug therapies aimed at correcting the underlying defect, modulators of the CFTR channel protein, have come onto the market, leading to a substantial clinical improvement in PwCF, modifying disease progression [ 64 , 65 ]. Evidence shows that restoration of CFTR channel protein function is associated with improved mucociliary clearance, and airway surface hydration, enhancing endogenous defence mechanisms by influencing the microbiology and response to bacterial infections in CF airways.…”
Section: Discussionmentioning
confidence: 99%
“…ACE polymorphisms have additionally been related to COVID-19, as studies have indicated that patients with the ACE D/D polymorphism showcase advanced medical signs and symptoms and a higher danger of lung damage in comparison to people with I/I or D/I polymorphisms (Karakaş Çelik et al, 2021 ). Furthermore, studies have validated that ACE polymorphisms can affect ACE2 expression, leading to the CF phenotype and pulmonary inflammation associated with the development of COVID-19 (Vitiello et al, 2023 ). It is critical to highlight that the angiotensin-converting enzyme 2 (ACE2) serves as the crucial host receptor for SARS-CoV-2 entry via the spike (S) protein on the virus surface (Zhang et al, 2020 ).…”
Section: Effect Of Host Factors Of Cf Patients On Sars-cov-2 Infectionmentioning
confidence: 99%
“…To ensure proper follow-up, facilities reached out to individuals showing symptoms indicative of COVID-19. According to a recent publication (Tedbury et al, 2023 ), CFTR may additionally affect the severity of SARS-CoV-2 infection and COVID-19 ailments in CF patients (Vitiello et al, 2023 ). Meanwhile, a literature evaluation (Marques et al, 2023 ) emphasizes the restricted understanding regarding the effects of COVID-19 on CF patients.…”
Section: Impact Of Covid-19 On Individuals With Cystic Fibrosismentioning
confidence: 99%